Dissolved hyperpolarized xenon‐129 MRI in human kidneys. Issue 1 (9th August 2019) - Chacon‐Caldera, Jorge; Maunder, Adam; Rao, Madhwesha; Norquay, Graham; Rodgers, Oliver I.; Clemence, Matthew; Puddu, Claudio; Schad, Lothar R.; Wild, Jim M.
Abstract : Purpose: To assess the feasibility of using dissolved hyperpolarized xenon‐129 ( 129 Xe) MRI to study renal physiology in humans at 3 T. Methods: Using a flexible transceiver RF coil, dynamic and spatially resolved 129 Xe spectroscopy was performed in the abdomen after inhalation of hyperpolarized 129 Xe gas with 3 healthy male volunteers. A transmit‐only receive‐only RF coil array was purpose‐built to focus RF excitation and enhance sensitivity for dynamic imaging of 129 Xe uptake in the kidneys using spoiled gradient echo and balanced steady‐state sequences. Results: Using spatially resolved spectroscopy, different magnitudes of signal from 129 Xe dissolved in red blood cells and tissue/plasma could be identified in the kidneys and the aorta. The spectra from both kidneys showed peaks with similar amplitudes and chemical shift values. Imaging with the purpose‐built coil array was shown to provide more than a 3‐fold higher SNR in the kidneys when compared with surrounding tissues, while further physiological information from the dissolved 129 Xe in the lungs and in transit to the kidneys was provided with the transceiver coil. The signal of dissolved hyperpolarized 129 Xe could be imaged with both tested sequences for about 40 seconds after inhalation. Conclusion: The uptake of 129 Xe dissolved in the human kidneys was measured with spectroscopic and imaging experiments, demonstrating the potential of hyperpolarized 129 Xe MR as a novel, noninvasive technique to image human kidney tissue perfusion.